Replacement of old flotation cells in the flotation plant of the Lece mine - Lazić, Predrag; Nikšić, Đurica; Stojanović, Dejan (Tehnika (Beograd), 2021)
Russian made FPM-GMO-1.6 flotation machines were previously installed for primary stage flotation concentration of lead and zinc minerals in Lece flotation plant. For cleaning stage FMR-10 flotation machines were in use. Beside low technological characteristic, hard maintenance and worn out are characteristic of this machines. In order to modernize the production and eliminate the above shortcomings primarily in the process of lead minerals flotation, in 2020, the old flotation cells were replaced with new ones. Currently, 8 new RCS-5 cells for coarse and scavengel flotation of lead minerals and 4 RCS-3 cells for cleaning of coarse lead mineral concentrate are working on the lead flotation line in Lece flotation. These cells were produced by Metso Minerals from Finland. Flotation cells, which are installed, have modern technical - technological characteristics, with all the accompanying equipment for automatic control of pulp levels and air consumption. This paper presents comparative characteristics of old and new flotation cells, their appearance and characteristics and technological results achieved in flotation with old and new cells.